Characterization of plasma sprayed bioglass coatings on titanium - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2003)
Bioglass, 45S5 containing 45% SiO2, 6% P2O5, 24.5% CaO and 24.5% Na2O all in weight percent, was plasma sprayed onto a titanium substrate with and without 60 Al2O3 40 TiO2 as a bond coating. Mechanical properties were evaluated by following the ASTM C633 method and the microstructural characterization has been carried out by using scanning electron microscope. Results indicate that the bonding strength of bond coatings is three times higher than of the coatings that are directly applied to the surface. It has been observed that there is a uniform coating layer with a thickness of 110 mum and that there was not any reaction observed at the coating-metal interface.
Keywords: bioglass; plasma spray coating; titanium; HYDROXYAPATITE COATINGS; IN-VITRO; COMPOSITES